THE ESSENCE OF CYBERSECURITY THROUGH FINTECH 3.5 IN PREVENTING AND DETECTING FINANCIAL FRAUD: A LITERATURE REVIEW - Selvaraj, Nagasundari A/P (Electronic Journal of Business and Management, 2021)
The dramatic rise in cybercrime necessitates effective security measures within the evolving Fintech 3.5 landscape. As daily reliance on cyberspace for investments, money exchanges, and online purchases peaks, no organization is entirely bulletproof against threats. This literature review explores the critical role of cybersecurity, specifically aided by Artificial Intelligence (AI), in preventing and detecting financial fraud. The study delves into cybersecurity tools, applications, challenges, and the regulatory environment that influences its function. It aims to provide a theoretical foundation for the complex IoT environments utilized by modern consumers while identifying future areas for research in the Fintech domain.